The promise of access : technology, inequality, and the political economy of hope - Greene, Daniel, 1973- (2021)
"Based on fieldwork at three distinct sites in Washington, DC, this book finds that the persistent problem of poverty is often framed as a problem of technology"--
Introduction: "The internet : your future depends on it" -- Discovering the divide : technology and poverty in the new economy -- The pivot and the trouble with 'tech' -- "More than just a building to sit in for the day" -- Flexible classrooms and charter schools -- Bootstrapping -- Conclusion: Reproducing hope.
Includes bibliographical references and index.
Shahana
Keywords: Digital divide -- Washington (D.C.); Computer literacy -- Social aspects -- Washington (D.C.); Knowledge economy -- Washington (D.C.); Poverty -- Washington (D.C.); Technology and state -- Washington (D.C.)